Effect of Azolla inclusion in the diet of Japanese quails on voluntary intake, apparent digestibility and egg production - Buenaño-Buenaño, Juan (2018)
The aim of this study was to evaluate the effect of the inclusion of Azolla on the diet of Japanese quails on voluntary intake, apparent nutrient digestibility and egg production. A total of 240 16-week old quail on the first third of egg laying were used. The birds were housed in 24 raised cages (10 per cage). A completely randomized design was used with four treatments: T1: 0%, T2: 5%, T3: 10% and T4: 15% inclusion of Azolla in the diet. Voluntary nutrient intake was higher in Azolla treatments (p<0.05). The lowest egg yield g/bird/day1 was in T4 (p<0.0001) and the best feed conversion was in T1 and T2 (p<0.0001). The apparent digestibility of dry matter and organic matter showed no significant difference between treatments. The highest crude protein digestibility was in T1 (46.1%) and T2 (44.5%) (p<0.0001) and the highest for digestibility of neutral detergent fibre was in T2 (63.6%) (p=0.034). The incorporation of Azolla by 5% in the quail diet produces a similar effect in egg production and feed conversion than the control diet, which could be used as a non-conventional low-cost product.